Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

(2((x+1) ^3 – (x+1) ^2 + (x+1)) )+3

Sagot :

( x + 1 )^3 = x^3 + 3x^2 +3x + 1;
(x + 1 )^2 = x^2 + 2x + 1;
=> (2((x+1) ^3 – (x+1) ^2 + (x+1)) )+3 =2( x^3 + 3x^2 +3x + 1 - x^2 -2x - 1 + x + 1 ) + 3 = 2( x^3 + 2x^2 + 2x + 1 ) + 3 =
= 2x^3 +4x^2 +4x + 5.